2017
DOI: 10.25081/jsa.2017.v1.59
|View full text |Cite
|
Sign up to set email alerts
|

Salinity influences physiological traits of seven Sesame (Sesamum indicum L.) varieties

Abstract: In the present investigation a pot culture experiment was conducted in order to estimate the effects of salt stress on some physiological traits in seven sesame varieties like PAIYUR-1, SVPR-1, TMV-3, TMV-4, TMV-5, VIR-1 and VIR-2. Young and fully matured leaves were taken from control and salinity treated plants on 15th Days After Treatment (DAT), 30th (DAT) and 45th (DAT) for all the experiments in different salinity (NaCl) concentrations of control, 40mM, 80mM, 120mM.During the experiments of photosynthetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…However, Kanagaraj and Desingh [29] showed in seven varieties of sesame a reduction in chlorophyll accompanied by a decrease in photosynthesis and the activity of photosynthetic enzymes following an increase in salinity. This drop in chlorophyll is due to the suppression of the enzymes responsible for its synthesis [30].…”
Section: Discussionmentioning
confidence: 97%
“…However, Kanagaraj and Desingh [29] showed in seven varieties of sesame a reduction in chlorophyll accompanied by a decrease in photosynthesis and the activity of photosynthetic enzymes following an increase in salinity. This drop in chlorophyll is due to the suppression of the enzymes responsible for its synthesis [30].…”
Section: Discussionmentioning
confidence: 97%
“…Salt stress was found to strongly inhibit the uptake and accumulation of N in different plant parts of green chireta, Andrographis paniculata [14]; cabbage, Brassica oleracea [19]; canola, Brassica napus [78]; cotton, Gossypium hirsutum [61]; gray poplar, Populus × canescens [20]; saltmarsh grass, Spartina alterniflora [65]; sesame, Sesamum indicum [79]; and wheat, Triticum aestivum [67]. However, the uptake and accumulation of N in response to salt stress depend on different plant and soil factors [80].…”
Section: Nitrogenmentioning
confidence: 99%
“…However, the uptake and accumulation of N in response to salt stress depend on different plant and soil factors [80]. Kanagaraj and Desingh [79] observed variations in foliar N among different varieties of sesame, where the maximum reduction was found at the highest dose of NaCl. The decline in the uptake of N by plants could be due to the increased uptake and accumulation of Cl.…”
Section: Nitrogenmentioning
confidence: 99%
“…When there is a decrease in salinity, plant roots will typically respond by absorbing more nitrate. When there is a rise in the concentration of salt in the soil, this phenomenon takes place [22,23]. ROS are primarily found in the chloroplast, mitochondria, and peroxisome as a harmful consequence of aerobic metabolism [24,25], and others have shown that increased generation of these reactive oxygen species (ROS) leads to lipid peroxidation, which in turn disrupts photosynthesis and membrane permeability and destroys nucleic acids, inhibits enzymes, and activates programmed cell death [26].…”
Section: The Harmful Effects Of Salinity On Plant Growthmentioning
confidence: 99%